Interaction network and localization of Brucella abortus membrane proteins involved in the synthesis, transport, and succinylation of cyclic β-1,2-glucans - Guidolin, Leticia Soledad (2015)
Cyclic β-1,2-glucans (CβG) are periplasmic homopolysaccharides that play an important role in the virulence and interaction of Brucella with the host. Once synthesized in the cytoplasm by the CβG synthase (Cgs), CβG are transported to the periplasm by the CβG transporter (Cgt) and succinylated by the CβG modifier enzyme (Cgm). Here, we used a bacterial two-hybrid system and coimmunoprecipitation techniques to study the interaction network between these three integral inner membrane proteins. Our results indicate that Cgs, Cgt, and Cgm can form both homotypic and heterotypic interactions. Analyses carried out with Cgs mutants revealed that the N-terminal region of the protein (Cgs region 1 to 418) is required to sustain the interactions with Cgt and Cgm as well as with itself. We demonstrated by single-cell fluorescence analysis that in Brucella, Cgs and Cgt are focally distributed in the membrane, particularly at the cell poles, whereas Cgm is mostly distributed throughout the membrane with a slight accumulation at the poles colocalizing with the other partners. In summary, our results demonstrate that Cgs, Cgt, and Cgm form a membrane-associated biosynthetic complex. We propose that the formation of a membrane complex could serve as a mechanism to ensure the fidelity of CβG biosynthesis by coordinating their synthesis with the transport and modification.